2018
DOI: 10.1515/biol-2018-0066
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Phage to Control Vancomycin Resistant Enterococcus faecium

Abstract: Enterococcus faecium, is an important nosocomial pathogen with increased incidence of multidrug resistance (MDR) – specifically Vancomycin resistance. E. faecium constitutes the normal microbiota of the human intestine as well as exists in the hospitals and sewage, thus making the microorganism difficult to eliminate. Phage therapy has gained attention for controlling bacterial MDR infections and contaminations. We have successfully isolated from waste water and characterized a lytic bacteriophage STH1 capable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…The optimum temperature for the biological activity of phage S2 was 37°C; however, the plaque formation decreased with increasing temperature from 37°C to 55°C but phage S2 exhibited acceptable stability in this temperature range. These findings are in agreement with previous studies (24,34). In this study, phage stability was investigated in a wide range of pH values (from 1 to 11).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The optimum temperature for the biological activity of phage S2 was 37°C; however, the plaque formation decreased with increasing temperature from 37°C to 55°C but phage S2 exhibited acceptable stability in this temperature range. These findings are in agreement with previous studies (24,34). In this study, phage stability was investigated in a wide range of pH values (from 1 to 11).…”
Section: Discussionsupporting
confidence: 94%
“…According to the results, phage S2 required 10 mM Mg 2+ for maximum infectivity, while the presence of Ca 2+ had no significant effect on phage uptake. Similar to our report, Taskeen Raza et al (2018) reported that Mg 2+ significantly increased phage uptake into the host cell and improved plaque formation (24). In contrast to our study, Sidra Rahmat Ullah et al reported that the addition of Ca 2+ affected phage SRG1 absorption (34).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…12 13 14 15 Of nine types of vancomycin-related operons/genetic elements ( vanA , vanB , van C1/C2/C3 , vanD , vanE , vanG , vanL , vanM , and vanN ), associated with glycopeptide-resistance in enterococci, van A , and van B are by far the most prevalent types and E. faecium is the predominant species of GRE. 8 9 10 11…”
Section: Introductionmentioning
confidence: 99%